1980
DOI: 10.1128/jvi.35.2.371-381.1980
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transcription of a Compact Nucleoprotein Complex Isolated from Purified Simian Virus 40 Virions

Abstract: Simian virus 40 (SV40) virions were dissociated in vitro by treatment with ethylene glycol-bis- N-N′ -tetraacetic acid and dithiothreitol. The compact nucleo-protein core released as a result of the dissociation had a sedimentation value of 110 to 115S compared with a value of 240S for intact virions. The viral cores contained a fraction of the viral proteins VP 1 and VP 2 in addition to the proteins found associated with the viral minichr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…We have recently reported that extracellular SV40 viral chromatin, which is similar to transcriptionally active eucaryotic genes, has a "relaxed" chromatin structure which makes the viral DNA highly accessible to enzymatic activities (4, 5). The conversion of SV40 chromatin to the relaxed conformation occurs as intracellular 75S chromatin sequentially matures into a 200S previrion, a 240S nuclear virion, and finally an extracellular virion (4,5,11,23). These studies demonstrate that the maturation process is accompanied by significant changes in chromatin composition, including increased acetylation of histones H3 and H4, the loss of histone H1, and the specific association of nonhistone viral protein with the chromatin complex.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…We have recently reported that extracellular SV40 viral chromatin, which is similar to transcriptionally active eucaryotic genes, has a "relaxed" chromatin structure which makes the viral DNA highly accessible to enzymatic activities (4, 5). The conversion of SV40 chromatin to the relaxed conformation occurs as intracellular 75S chromatin sequentially matures into a 200S previrion, a 240S nuclear virion, and finally an extracellular virion (4,5,11,23). These studies demonstrate that the maturation process is accompanied by significant changes in chromatin composition, including increased acetylation of histones H3 and H4, the loss of histone H1, and the specific association of nonhistone viral protein with the chromatin complex.…”
Section: Resultsmentioning
confidence: 84%
“…The lengths of all RNA transcril corrected by 5.6% to compensate for migration rates of RNA and DNA molecu gels. 5). Similar of 3,450, 1,600, and 1,460 nucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ocsngwa n0h horiontl dmenion wit acdit inreaing romlef torigt. SS-PGE as n te veticl dmenion Aferth irt-ienioa fcuin,th gl wreeuiibatdan eetrphrse i teseon imnso as dscried y O'arrll (5). (A) utordioraphof olyoa cpsid aftr FIG.…”
Section: Ief Of "2'i-labeled Virions and Capsidsmentioning
confidence: 99%